Dichotomous key for identification of Indian sandfly species (Diptera:Phlebotomidae ) - Geeta Maheshwari (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2008)
Sandflies are the tiny haematophagous dipter insects of suborder Nematocera belonging to family Phlebotomidae, subfamily Phlebotominae. Fauna of Indian sub-zone is represented by 46 species, of these, 11 belong to Phlebotomus species and 35 to Sergentomyia species. Various classification systems for phlebotomine sandflies have been proposed since Newstead 1911, inclusive of the classifications given by Abonnenc, Davidson, Fairchild, Leng, Lewis, Quate, and Theodor. However, despite this immense literary work, there is no universal concurrence regarding the ranking of taxa above the species level.Therefore, A key is being formulated for Indian elements and the key has been run many time to confirm its validity.